Basagran® induces developmental malformations and changes the bacterial community of zebrafish embryos - Oliveira, Jacinta M. M. (2020)
This study aimed to assess the effects of Basagran® on zebrafish (Danio rerio) embryos. The embryos were exposed to Basagran® at concentrations ranging from 120.0 to 480.6 mg/L, and the effects on embryo development (up to 96 h) and bacterial communities of 96 h-larvae were assessed. The embryo development response was time-dependent and concentration-dependent (106.35 < EC50 < 421.58 mg/L). The sensitivity of embryo-related endpoints decreased as follows: blood clotting in the head and/or around the yolk sac > delay or anomaly in yolk sac absorption > change in swimming equilibrium > development of pericardial and/or yolk sac oedema > scoliosis. A PCR-DGGE analysis was used to evaluate changes in the structure, richness, evenness and diversity of bacterial communities after herbicide exposure. A herbicide-induced structural adjustment of bacterial community was observed. In this study, it was successfully demonstrated that Basagran® affected zebrafish embryos and associated bacterial communities, showing time-dependent and concentration-dependent embryos' developmental response and structural changes in bacterial community. Thus, this work provides for the first time a complementary approach, which is useful to derive robust toxicity thresholds considering the embryo-microbiota system as a whole. The aquatic hazard assessment will be strengthened by combining current ecotoxicological tests with molecular microbiology tools.